Perspektif PBB Mengenai Pelanggaran Human Security Perempuan Oleh Taliban 2021 - Gili Argenti; Sultan Dhiaulhaq; Arditta Pramesti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Taliban, which means “students” in the Pashto language. They emerged in the early 1990s in northern Pakistan. Fought alongside the Mujahideen which is Afghan rebels after Soviet occupation. Majority of the Taliban members had studied in conservative religious schools in Afghanistan and across the border in Pakistan. In 1996, the Taliban seized Kabul, the capital city. At that time, they hanged Najibullah Ahmaddzai who was the last communist president of Afghanistan. The Taliban enforcing traditional Islamist rules and confining women to their homes. Women from conservative communities also perceived western, modern influences are wrong, it made the patriarchal culture continue to develop in Afghanistan until it eventually led to discrimination of women's rights. The United Nations (UN) has an important role, that is assisting in the protection and enforcement of human rights in accordance with their duties. The UN had successfully ratified the universal declaration of human rights (UDHR) on December 10, 1948. This Convention discusses the elimination of all forms of discrimination, one of which is against the rights of women and children.